2008
DOI: 10.1002/ana.21480
|View full text |Cite
|
Sign up to set email alerts
|

Risk variants for atrial fibrillation on chromosome 4q25 associate with ischemic stroke

Abstract: We discovered that variants previously shown to associate with atrial fibrillation (AF), rs2200733 and rs10033464, significantly associated with IS, with the strongest risk for CES. The association with noncardiogenic stroke is intriguing and suggests that atrial fibrillation may be underdiagnosed in patients presenting with stroke. This discovery may have implications for workup and treatment of IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
185
2
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(202 citation statements)
references
References 31 publications
6
185
2
9
Order By: Relevance
“…13,14,[35][36][37] Importantly, in the largest meta-analysis to date, all associations were with ischaemic stroke subtypes, and these showed much stronger association than in an analysis with all ischaemic stroke (κ = 1.24, 1.23, 1.19, and 1.11 for rs2107595 (HDAC9), rs6843082 (PITX2), rs879324 (ZFHX3), and rs2383207 (9p21), respectively). 13 Further to this, analyses of early onset cases suggest even stronger associations with young onset cases at these loci.…”
Section: Discussionmentioning
confidence: 91%
“…13,14,[35][36][37] Importantly, in the largest meta-analysis to date, all associations were with ischaemic stroke subtypes, and these showed much stronger association than in an analysis with all ischaemic stroke (κ = 1.24, 1.23, 1.19, and 1.11 for rs2107595 (HDAC9), rs6843082 (PITX2), rs879324 (ZFHX3), and rs2383207 (9p21), respectively). 13 Further to this, analyses of early onset cases suggest even stronger associations with young onset cases at these loci.…”
Section: Discussionmentioning
confidence: 91%
“…Variants in two genes associated with atrial fibrillation, PITX2 and ZFHX3, were found to be independent risk factors for ischaemic stroke; 14,15 further analysis determined that these associations were specific to the development of cardioembolic stroke. 16 PITX2 encodes a transcription factor regulated by β-catenin, whereas ZFHX3 encodes a zinc finger protein.…”
Section: Early Studiesmentioning
confidence: 98%
“…18,19 The third and fifth most significant phenotypes in this PheWAS were atrial fibrillation codes (ICD9 427.31, P ¼ 2.1 Â 10 À4 ; ICD9 427.3, P ¼ 2.8 Â 10 À4 ; Figure 1d). This SNP has also been reported to be associated with ischemic stroke, 20 but the associations for the ICD9 codes describing cerebrovascular disease (ICD9 430-438) were not significant.…”
Section: Control Snpsmentioning
confidence: 87%